2, 4, 4, 8, 8‐Pentanitro‐2‐Azaadamantane: A High‐Density Energetic Compound. Issue 46 (14th December 2017) - Hou, Tianjiao; Ruan, Hongwei; Wang, Guixiang; Luo, Jun
Abstract : Polynitroazaadamantanes have a broad application prospect in the field of energetic materials. Herein, the synthesis of 2, 4, 4, 8, 8‐pentanitro‐2‐azaadamantane, a new member of the polynitroazaadamantane family, is described in detail. It was prepared through eleven steps in an overall yield of 8.8 %, starting from easily accessible compounds. It shows high thermal stability, an onset decomposition at 254 °C and high density (1.813 g·cm –3 ). Abstract : The novel high‐performance energetic material 2, 4, 4, 8, 8‐pentanitro‐2‐azaadamantane was synthesized in eleven steps from bicyclo[3.3.1]nonane‐2, 6‐dione.